Diagnostics in plant breeding - Leubberstedt, Thomas; Varshney, Rajeev K. (Springer, 2013)
“Diagnostics in Plant Breeding” is systematically organizing cutting-edge research reviews on the development and application of molecular tools for the prediction of plant performance. Given its significance for mankind and the available research resources, medical sciences are leading the area of molecular diagnostics, where DNA-based risk assessments for various diseases and biomarkers to determine their onset become increasingly available. So far, most research in plant genomics has been directed towards understanding the molecular basis of biological processes or phenotypic traits. From a plant breeding perspective, however, the main interest is in predicting optimal genotypes based on molecular information for more time- and cost-efficient breeding schemes. It is anticipated that progress in plant genomics and in particular sequence technology made recently will shift the focus from “explanatory” to “predictive” in crop science. This book assembles chapters on all areas relevant to development and application of predictive molecular tools in plant breeding by leading authorties in the respective areas.--Provided by publisher.